The Role of Continuous Peripheral Nerve Blocks - José Aguirre; Alicia Del Moral; Irina Cobo; Alain Borgeat; Stephan Blumenthal (Anesthesiology Research and Practice)
A continuous peripheral nerve block (cPNB) is provided in the hospital and ambulatory setting. The most common use of CPNBs is in the peri- and postoperative period but different indications have been described like the treatment of chronic pain such as cancer-induced pain, complex regional pain syndrome or phantom limb pain. The documented benefits strongly depend on the analgesia quality and include decreasing baseline/dynamic pain, reducing additional analgesic requirements, decrease of postoperative joint inflammation and inflammatory markers, sleep disturbances and opioid-related side effects, increase of patient satisfaction and ambulation/functioning improvement, an accelerated resumption of passive joint range-of-motion, reducing time until discharge readiness, decrease in blood loss/blood transfusions, potential reduction of the incidence of postsurgical chronic pain and reduction of costs. Evidence deriving from randomized controlled trials suggests that in some situations there are also prolonged benefits of regional anesthesia after catheter removal in addition to the immediate postoperative effects. Unfortunately, there are only few data demonstrating benefits after catheter removal and the evidence of medium- or long-term improvements in health-related quality of life measures is still lacking. This review will give an overview of the advantages and adverse effects of cPNBs.